PERAN MEDIASI REPUTASI RUMAH SAKIT PADA PENGARUH RELATIONSHIP MARKETING,PERSEPSI NILAI, DAN INOVASI TERHADAP ELECTRONIC WORD OF MOUTH - Indah Kurniawati; Dini Handayani; Erry Yudhya Mulyani (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to analyze the influence of relationship marketing, perceived value, and service innovation on electronic word of mouth (eWOM) with hospital reputation as a mediating variable at Tzu Chi Hospital PIK. This study used a quantitative approach with a survey distributed to 200 patients. Data were analyzed using SEM-AMOS to test the relationship between variables, and the Three-Box Method to map variable performance based on respondents' perception indices. The results showed that simultaneously, relationship marketing, perceived value, and service innovation, through hospital reputation, had a positive and significant effect on eWOM. Partially, relationship marketing, perceived value, and service innovation had a significant positive effect on eWOM. Relationship marketing and service innovation had a positive and significant effect on hospital reputation, while perceived value had no effect. Hospital reputation also had a significant positive effect on eWOM but did not mediate the relationship between the variables. These findings suggest that patient eWOM is influenced by factors other than those in the research model. The Three-Box Method results showed that all variables were in the high category, although several indicators still had relatively low scores. This study implies that eWOM in the healthcare sector is not only influenced by relationships, values, and service innovation, but also by other factors such as patient emotional experiences, personal interactions, and the quality of digital communication.